Opacification of hydrophilic intraocular lenses after Descemet stripping automated endothelial keratoplasty - Morgan-Warren, Peter J (Clin Ophthalmol, 2015)
PURPOSE: Opacification of hydrophilic acrylic intraocular lenses (IOLs) is an emerging complication following Descemet stripping automated endothelial keratoplasty (DSAEK). We report six cases and review the current literature. METHODS: In this retrospective, noncomparative, observational case series, patients with IOL opacification after previous DSAEK surgery were identified from corneal clinic records. Case notes were reviewed for demographic details, indication for DSAEK, IOL model, incidence of rebubbling, and postoperative course. RESULTS: Six patients developed IOL opacification after DSAEK. All patients had Fuchs’ endothelial dystrophy and had previously received hydrophilic acrylic IOL models. Central anterior IOL opacification was noted in all six cases. Five cases (83%) had required rebubbling due to dislocated graft tissue, and one had an early postoperative intraocular pressure (IOP) rise. Five cases (83%) were managed conservatively, and one case with a failed graft underwent redo DSAEK and IOL exchange. CONCLUSION: Repeated exposure to intracameral air, raised IOP, and other patient influences may be major etiological factors for IOL opacification after DSAEK. We advise avoiding hydrophilic acrylic IOL models in patients who may require future endothelial keratoplasty.